Rehabilitation after autologous chondrocyte implantation in athletes - Nho, S. J.; Pensak, M. J.; Seigerman, D. A.; Cole, B. J. (Clinics in Sports Medicine, 2010)
Over the years a variety of cartilage restorative procedures have been developed for athletes to address focal, full-thickness cartilaginous defects in the knee joint, including microfracture, osteochondral autografts, osteochondral allografts, autologous chondrocyte implantation (ACI), and most recently, next-generation ACI involving scaffolds or cell-seeded scaffolds. Since its introduction, ACI has yielded some very promising results in athletes and nonathletes alike. Rehabilitation following ACI requires an in-depth understanding of joint mechanics, and knowledge of the biologic and biomechanical properties of healing articular cartilage. A patient-, lesion-, and sports-specific approach is required on the part of the trainer or physical therapist to gradually restore knee joint function and strength so that the athlete may be able to return to competitive play. This article reviews the rehabilitation protocols for injured athletes following an ACI procedure.